Implementasi Pembelajaran Tahfidzul Qur’an dalam Pembentukan Karakter Religius dan Disiplin Siswa di SMP NU Darussalamah Braja Harjosari - Sari, Hana Juita Purnama; Hadi, Mukhtar; Zumaro, Ahmad (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
This study aims to analyze how the Qur'an memorization (Tahfidzul Qur'an) learning program at SMP NU Darussalamah Braja Harjosari contributes to the development of students' religious character and discipline. Tahfidzul Qur'an not only focuses on improving memorization but also plays a role in instilling religious values and discipline. The research method used is qualitative with a descriptive approach, collecting data through observations, interviews, and documentation involving the school principal, Tahfidz teachers, and students. The Tahfidz learning at this school applies the Wahdah, Sima’i, Jama’, and Muraja’ah methods, which are implemented in a structured daily, weekly, and monthly program. The research findings show that the Tahfidzul Qur'an learning program significantly contributes to shaping students' religious character, which is reflected in their awareness of worship, adherence to religious teachings, and good moral conduct (akhlakul karimah). Furthermore, students' discipline has improved through the memorization routine and adherence to the memorization schedule. However, there are several challenges, such as differences in students' memorization abilities, limited time due to a packed academic schedule, and a lack of support from families in maintaining memorization outside of school.